1998
DOI: 10.1046/j.1469-8137.1998.00310.x
|View full text |Cite
|
Sign up to set email alerts
|

Association between microtubules and symbiotic fungal hyphae in protocorm cells of the orchid species, Spiranthes sinensis

Abstract: Seeds of the orchid species, Spiranthes sinensis (Pers.) Ames, were sterilized and germinated in vitro with the symbiotic fungus Ceratobasidium cornigerum (Bourdot) Rogers. Colonized embryos developed into protocorms and these were examined for changes in microtubule arrays, after initial invasion of fungal hyphae into embryos and during peloton formation and degradation. Methods utilized to detect microtubules included immunofluorescence combined with laser scanning confocal microscopy, conventional tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The amyloplasts in a cell lost starch when the cell was colonized; C from the starch was mobilized and allocated to the meristematic cells, perhaps together with newly obtained fungal C. When the peloton was degraded to form a fungal clump, starch synthesis was restarted in proplastids, and concurrently r13C elevation occurred in cell wall regions. Cytological changes in the same cycle were previously found in the modification of arrays of cortical microtubules (Uetake et al ., ; Uetake & Peterson, ) and the activity of adenylate cyclase (an enzyme that catalyzes the conversion of ATP to 3′5′‐cyclic AMP and pyrophosphate) localized on host membranes (Uetake & Ishizaka, ; Table ). These studies showed functional similarities between the membranes surrounding young and senescent hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…The amyloplasts in a cell lost starch when the cell was colonized; C from the starch was mobilized and allocated to the meristematic cells, perhaps together with newly obtained fungal C. When the peloton was degraded to form a fungal clump, starch synthesis was restarted in proplastids, and concurrently r13C elevation occurred in cell wall regions. Cytological changes in the same cycle were previously found in the modification of arrays of cortical microtubules (Uetake et al ., ; Uetake & Peterson, ) and the activity of adenylate cyclase (an enzyme that catalyzes the conversion of ATP to 3′5′‐cyclic AMP and pyrophosphate) localized on host membranes (Uetake & Ishizaka, ; Table ). These studies showed functional similarities between the membranes surrounding young and senescent hyphae.…”
Section: Discussionmentioning
confidence: 99%
“…The plant-fungal interface consists of the fungal plasma membrane and cell wall surrounded by the perifungal membrane (derived from the host plasma membrane), and has a high surface-to-volume ratio, as is appropriate for a site of intense molecular exchange. The application of immunofluorescence labelling shows that after root cell invasion by fungal hyphae, the organization of plant microtubules is altered substantially and a microtubule array assembles adjacent to the perifungal membrane (Genre and Bonfante, 1997;Uetake et al, 1997;Uetake and Peterson, 1998;Genre and Bonfante, 1998;Matsubara et al, 1999;Blancaflor et al, 2001;Genre and Bonfante, 2002;Armstrong and Peterson, 2002).…”
Section: Responses To Mycorrhizal Fungimentioning
confidence: 99%
“…Microtubule arrangement alters in response to external stimuli such as electrical fields, gravity and heat stress (Blackman & Overall, 1995; Smertenko et al ., 1997; Himmelspach et al ., 1999) and may regulate stomatal movements (Fukuda et al ., 1998). Microtubules are also intimately associated with the formation and maintenance of the inter‐ and intracellular structures of mycorrhizal fungi (Carnero Diaz et al ., 1996; Genre & Bonfante, 1998; Uetake & Peterson, 1998; Matsubara et al ., 1999). Alterations to microtubule arrangement within plant cells have also been associated with a number of infection‐induced changes that occur during pathogen challenge.…”
Section: Introductionmentioning
confidence: 99%